Genetic Tests for Depression Treatment - Lahutina, Sofiia (Psychosomatic Medicine and General Practice, 2019)
Nowadays, a third of people with depression are treatment-resistant. Even in the best-case scenario, common antidepressants might take six weeks or more to kick in. Relatively few studies have examined the association between genetic variations and outcomes in patients treated with alternative antidepressants. Genetic tests for depression hit the market 10 years ago, but have surged in popularity in the last five years. The era of pharmacogenomic testing has just begun and psychiatrists predict that, given more research, they may one-day guide decision-making in the clinic.